Indigenous self-determination in fisheries governance: implications from New Zealand and Atlantic Canada - Bodwitch, Hekia; Hamelin, Kayla M.; Paul, Kenneth; Reid, John; Bailey, Megan (Frontiers in Marine Science, 2024)
The United Nations’ Declaration on the Rights of Indigenous Peoples (UNDRIP) recognized Indigenous rights to self-determination. How these rights can be realized in territories governed by settler-states remains unclear. For fisheries, the need to understand processes that support Indigenous self-determination has gained urgency due to government commitments and investor interest in developing ocean and coastal resources, or Blue Economies, amid rapid climatic changes. Here, we explored Indigenous groups’ fishery development experiences following two approaches to reconciling Indigenous fishing rights. In New Zealand, we examined Māori groups’ experiences following the 1992 Treaty of Waitangi (Fisheries Claims) Settlement Act. The Settlement granted Māori iwi (tribes) rights to self-govern non-commercial harvests, restrict fishing pressure in state-approved customary fishing areas, and participate in state-run systems for commercial fisheries management. In Canada, we investigated Indigenous fishery development initiatives following the Supreme Court of Canada’s 1999 ruling R. v. Marshall. Marshall reaffirmed Treaty-protected rights to harvest and trade fish, held by Mi’kmaq, Wolastoqey, and Peskotomuhkati Peoples, to support a “moderate livelihood.” We document how, in both cases, Indigenous groups’ self-determination remains constrained by actions from state regulatory and enforcement agencies that govern market access, other resource users’ activities, and processes for collecting and sharing information about fish populations. Indigenous groups’ experiences highlight that: 1) reallocations of harvest rights, on their own, are an insufficient means to redistribute access to benefits from fisheries; 2) the constraints Indigenous families have experienced in their attempts to develop small-scale fishing operations correspond to settler-state policies and cannot be addressed solely through changes to Indigenous leaders’ management decisions; and 3) polycentricity in governance regimes can pose problems for Indigenous self-determination, when citizens with political authority resist efforts to support Indigenous fisheries. To address these challenges, we call for legal reforms that require settler-state governments to support Indigenous self-determination, to overcome the political risks politicians face when advocating for a non-majority group’s interests.